2014
DOI: 10.1007/s00253-014-6021-z
|View full text |Cite
|
Sign up to set email alerts
|

TAT-RhoGDI2, a novel tumor metastasis suppressor fusion protein: expression, purification and functional evaluation

Abstract: Rho GDP dissociation inhibitor 2 (RhoGDI2) was identified as a functional metastasis suppressor in human bladder cancer, suggesting that increasing the RhoGDI2 level may represent a promising therapeutic strategy. It has been shown that the transactivator of transcription (TAT) protein from HIV-1 is able to efficiently deliver various biological molecules into several cell types. In this study, TAT peptide was fused with the N-terminus of RhoGDI2, and the resulting TAT-RhoGDI2 fragment was inserted into the pG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The adenovirus associated virus (AAV), a single-stranded DNA virus with an icosahedral capsid, is a promising vector for gene transferring in vivo 19 . The transactivator of transcription (TAT) protein from human immunodeficiency virus (HIV)-1, an 11-amino acid peptide, is an excellent candidate for protein transduction which could fuse with other proteins to improve their penetration 20 21 . The HA2, a subunit of the influenza A virus hemagglutinin glycoprotein HA, includes a hydrophobic peptide sequence which could facilitate lipid membrane destabilization 22 23 .…”
mentioning
confidence: 99%
“…The adenovirus associated virus (AAV), a single-stranded DNA virus with an icosahedral capsid, is a promising vector for gene transferring in vivo 19 . The transactivator of transcription (TAT) protein from human immunodeficiency virus (HIV)-1, an 11-amino acid peptide, is an excellent candidate for protein transduction which could fuse with other proteins to improve their penetration 20 21 . The HA2, a subunit of the influenza A virus hemagglutinin glycoprotein HA, includes a hydrophobic peptide sequence which could facilitate lipid membrane destabilization 22 23 .…”
mentioning
confidence: 99%
“…25, 26 The core region of Tat comprises a basic amino acid domain that contains six arginines and two lysines. 27, 28, 29 The current study showed that the transmembrane transduction efficiency of heterologous proteins was immediately affected by the number of amino acids. The prediction of protein secondary structure results showed that the α-helix structure could be formed in the Tat basic amino acid domain.…”
Section: Discussionmentioning
confidence: 64%
“…HA2 is a subunit of the hemagglutinin glycoprotein protein HA of the influenza A virus, including a hydrophobic peptide segment, that promotes lipid membrane instability [14]. TAT is an 11-amino acid peptide fragment of HIV-1, has a protein-transport function, and can fuse to other proteins to increase penetrability [15,16]. In our previous study, we successfully constructed BDNF-HA2TAT/AAV [17,18].…”
Section: Introductionmentioning
confidence: 99%